Fenomenologi Cancel Culture: Persepsi Netizen terhadap Citra Abidzar Al-Ghifari di Media Sosial - Basari, Rambang (LITERATUS, 2025)
The phenomenon of cancel culture in the digital age has become increasingly prominent, serving as a form of social expression used by netizens to express their disapproval of the actions of public figures. This study aims to uncover netizens' perceptions of Abidzar Al-Ghifari's image following the occurrence of cancel culture through social media. Using a phenomenological approach, data was collected through in-depth interviews with 15 active netizens on Instagram and Twitter who had previously expressed opinions about Abidzar. The findings indicate that cancel culture is understood as a form of social control, an expression of dissatisfaction, and can also have psychological impacts on both the targeted individual and the netizens themselves. This study offers new insights into how public image is constructed, criticized, and dismantled within the context of digital communication.